2015
DOI: 10.1136/bmjopen-2015-009235
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve the appropriate use of polypharmacy in older people: a Cochrane systematic review

Abstract: ObjectiveTo summarise the findings of an updated Cochrane review of interventions aimed at improving the appropriate use of polypharmacy in older people.DesignCochrane systematic review. Multiple electronic databases were searched including MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (from inception to November 2013). Hand searching of references was also performed. Randomised controlled trials (RCTs), controlled clinical trials, controlled before-and-after studies and interrupted ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
227
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(252 citation statements)
references
References 42 publications
7
227
0
18
Order By: Relevance
“…1 Muitas RAM são evitáveis se houver uma preocupação com a identificação e a prevenção do uso de medicamentos potencialmente inapropriados (MPI) e de combinações indesejáveis. 4 Esse fato é de grande relevância clínica, em especial na população idosa, por diversos fatores:…”
Section: Introductionunclassified
“…1 Muitas RAM são evitáveis se houver uma preocupação com a identificação e a prevenção do uso de medicamentos potencialmente inapropriados (MPI) e de combinações indesejáveis. 4 Esse fato é de grande relevância clínica, em especial na população idosa, por diversos fatores:…”
Section: Introductionunclassified
“…Furthermore, polypharmacy impacts significantly health outcomes and healthcare resources. While traditionally polypharmacy has been classified in terms of the number of medicines (usually defined as the use of five or more medicines) [14], Patterson et al suggested, as part of a Cochrane review in 2012 (later updated in 2014), that there should be a change in emphasis from 'inappropriate polypharmacy' (prescribing of multiple medicines which are either inappropriate or no longer indicated) to 'appropriate' or 'optimal polypharmacy' (appropriate prescribing of multiple medicines) [15][16][17].…”
Section: Polypharmacymentioning
confidence: 99%
“…The review findings were based upon ten papers, with the authors concluding that, while there is uncertainty about the elements of intervention that impact positively appropriate polypharmacy, pharmaceutical care appears to improve prescribing [16,17].…”
Section: Managing Inappropriate Polypharmacymentioning
confidence: 99%
See 2 more Smart Citations